Comparative Plasma Protein Profiling of Hemoglobin H Disease. (15th June 2014) - Leecharoenkiat, Kamonlak; Sornjai, Wannapa; Khungwanmaythawee, Kornpat; Paemanee, Atchara; Chaichana, Chartchai; Roytrakul, Sittiruk; Fucharoen, Suthat; Svasti, Saovaros; Smith, Duncan R.
Abstract : HbH and HbH-constant spring (HbH-CS) are the most common forms of α -thalassemia detected in the Thai population. The accumulation of excess β globin chains in these diseases results in increased red cell hemolysis, and patients with HbH-CS normally have a more severe clinical presentation than patients with HbH disease. This study aimed to detect alterations in the expression of plasma proteins of HbH and HbH-CS patients as compared to normal plasma. Platelet poor plasma was separated from HbH and HbH-CS and normal subjects and differential plasma proteins were detected using two-dimensional gel electrophoresis and identified using LC/MS/MS. A total of 14 differentially expressed proteins were detected of which 5 proteins were upregulated and 9 were downregulated. Most of the differentially expressed proteins are liver secreted proteins involved in hemolysis, oxidative stress response, and hemoglobin degradation. Seven proteins were found to be differentially expressed between HbH and HbH-CS. Levels of haptoglobin, a hemoglobin scavenging protein, were significantly increased in HbH patients as compared to HbH-CS patients. The identification of differentially expressed proteins may lead to a better understanding of the biological events underlying the clinical presentation of HbH and HbH-CS patients and can have application as hemolytic markers or severity predictors.